Creación de la marca territorial del cantón Guamote para generar posicionamiento en el público interno y externo en el periodo 2015 – 2016. - Saltos Costales, Evelyn Daniela (2016)
In the complex and changing environment in which we live, competition between brands is not generated in the outlets, are they virtual or real. The city brand is of great value to the management of municipal Marketing, as it represents a set of strengths and weaknesses linked to images we have of the place of origin incorporating or decreasing the value provided by a brand of a product or service. The "brand" for the Guamote canton is the marketing strategy that posed as a tool for promoting the destination and constitutive element of competitiveness. This proposal arose from the knowledge of the "Brand" instrument used in other cities in the province of Ecuador; the analysis prepared to suggest that there is growing interest in architecture, tourism as a complementary economic activity, allowing greater local development. In the first instance a theoretical framework in which it was possible to list key concepts for the understanding of what "brand" and other relevant terms related to research methodologies such as literature search on the Internet, was developed and a survey in books, magazines of the canton. It is essential to show that this city does not have a mark that identifies you from the other cities and determine how an improvement in the perception of image and positioning them through their promotion can help increase demand, it was necessary to establish the attractions which count the municipality. Finally I established what could be those guidelines to follow to create a "city brand" for the Guamote, which is my proposal itself "brand".